SISTEM PENYALURAN TENAGA KERJA ONLINE MELALUI BURSA KERJA KHUSUS (BKK) DI SMK PGRI 2 WONOGIRI - Yohanes Aris Supriatno, Bebas Widada, Tri Irawati (Jurnal Ilmiah SINUS, 2015)
BKK SMK PGRI 2 Wonogiri is a means to help post graduate, especially graduate of SMK PGRI 2 Wonogiri to obtain information about current job needs . It also BKK SMK PGRI 2 Wonogiri can be a means for DU / DI to find candidates for employment in the database needs and requirements. We make information systems BKK SMK PGRI 2 Wonogiri web based is expected to help provide information to alumni of SMK / SMA equal in Wonogiri and the surrounding region . Keywords : job , BKK , the distribution of labor